Polemik Undang-Undang Informasi Dan Transaksi Elektronik Yang Bertentangan Dengan Prinsip The Rule Of Law - Athar Tristan Andana Kanz; Reza Yuda Sakti; Romauli Yohana Sinaga; Serlin Lovina Manalu (International Forum of Researchers and Lecturers, 2023)
Rule of Law is a basic principle in a legal system where the law applies equally to everyone, including the government and citizens, and no person or party is excluded from the law. It also emphasises that legal decisions must be based on existing laws and must be implemented fairly and consistently. The law is the highest norm that binds all other legal norms, thus becoming the foundation for state power and legal regulation within a country. The rule of law and the law are closely interrelated in a country's legal system. In a well-functioning legal system, the rule of law and the law work together to create justice and security for all citizens. The rule of law helps ensure that the government does not abuse its power or violate the rights of individuals. The purpose of this research is to analyse Law No. 11 of 2008 which has been amended into Law No. 19 of 2016 regarding Electronic Information and Transactions (ITE Law) which is not in accordance with the principles of The Rule of Law and how this ITE Law can reflect the principles of The Rule of Law. This research method is library research. The results of this study are the development of technology and information today makes the government then issue Law Number 11 of 2008 (ITE Law) concerning the use of technology as well as information, ITE Law prohibits all forms of criminal acts that violate using technology and information, such as information disseminated will get bad treatment for the community. In practice in Indonesia, there are several cases that contradict the principle of The Rule of Law, for example, the ITE Law can cause confusion due to the increasing total every year of technology and information users, so the use of technological facilities is also increasingly widespread plus the ITE Law until now has not been widely socialised to the public.